Tracking amino acid’s uptake into the protozoan Acanthamoeba castellanii by stable-isotope labelling and Raman spectral imaging - Naemat, Abida; Elsheikha, Hany M.; Notingher, Ioan (Society of Photo-optical Instrumentation Engineers, 2016)
The capacity of pathogens to acquire nutrients from their host cells is one of the most fundamental aspects of infection biology. Hence, measuring the patterns of nutrients’ uptake by pathogens is essential for understanding the interactions of pathogens with eukaryotic host cells. In this study, we optimized a technique that allows fast and non-destructive measurement of the amino acid Phenylalanine (Phe) acquired by the trophozoite stage of the protozoan Acanthamoeba castellanii (A. castellanii) as they engage with individual human retinal pigment epithelial cells (ARPE-19). ARPE-19 host cells were pre-saturated with Deuterated Phe (L-Phe(D8)) to replace the native substrate Phe (L-Phe). The uptake of L-Phe(D8) by A. castellanii trophozoites was measured by Raman microspectroscopy. This approach allowed us to characterize the uptake patterns of this essential amino acid into A. castellanii trophozoites at a single cell level. At 24 hours post infection (PI) A. castellanii trophozoites are capable of salvaging L-Phe(D8) from host cells. The uptake pattern was time-dependent during the first 24 hours of infection and complete substitution with L-Phe(D8) in all parasites was detected at 48 hours PI. On the other hand, isolated A. castellanii trachyzoites (grown without host cells) did not show significant uptake for L-Phe(D8) from the media; only achieved an uptake ratio of 16-18% of L-Phe(D8) from the culture medium after 24 hours. These findings demonstrate the potential of combining Raman microspectroscopy and stable isotope labelling approaches to elucidate the role of metabolism in mediating A. castellanii interaction with host cells.